Evaluation the Effectiveness of Impregnated Net in Reducing Leishmaniasis Incidence: Diala-Iraq - Tawfeeq, Haifa I.; Abdul-Raheem, Yousif; Rasheed, Zuhair Najeeb; Rashid, Buthaina Ateyah (AL-Kindy College Medical Journal, 2010)
Background: Leishmaniasis is important public health problem owing to its impact on morbidity and mortality and difficulties in application of effective control measures. Objective: The aim of the study is to evaluate the using of impregnate bed nets in the control of leishmaniasis. Methods: The study was conducted throughout the years 2004 and 2005, in Diala Governorate (about 60km north-east Baghdad). This is the first study in Iraq for evaluation of the impregnated bed net in control of leishmaniasis. Two villages were selected to achieve this aim. The nets were distributed for the first village to be used by their population. The second village was served as control. Results: The results revealed that there was a significant decline in the incidence of cutaneous leishmaniasis from 19.23 per 1000 (before net distribution) to 3.34 per 1000 (after net distribution). On other hand, there was no significant difference in the incidence in the second village (control) as it was 13.42 to 12.46 per 1000. Conclusions: Impregnated bed net is effective in the reduction of leishmaniasis incidence when used properly as a control measures